Variabilidade espacial de atributos físicos e hídricos do solo e da produtividade da cultura da soja em uma área comercial - Scherpinski, Clementina (2005)
Studies that involve the physical attributes and hydrics of the soil are important for the development of the maintainable agriculture. When the areas of cultivated lands are used with intense agricultural production, the soil presents alterations in their physical attributes and hydrics. The economical viability of the agricultural production depends of these attributes and it requests more detailed studies about the space variability of the soils. Among the attributes hydrics stands out the Hydraulic Conductivity that is characterized by the easiness with that the water is driven through the soil and it is important for a good development of the agriculture. Nowadays, the Hydraulic Conductivity of the soil is one of the main parameters used for studies that involve the flow of water in the soil. This work has for objective to study the space variability of the physical attributes (bulk density, micro porosity, macro porosity, total porosity) and attributes hydrics (hydraulic conductivity, infiltration of the water in the soil of the soil) and of the productivity of the soy, with focus in Agriculture of Precision. It was looked for to understand the behavior of the attributes of the physical space, linked to the agricultural production of the soy in a commercial area in the West of Paraná. For the analyses of the attributes in study variograms and graph h-scatterplot were used for the verification of the structure of space dependence and construction of thematic maps through the ordinary kriging. For the verification of the space correlation of the physical attributes and hydrics studied with the productivity of the soy crossed variograms were built. In general all of the attributes presented space dependence except for the attribute Density of the Soil in the depth (0 - 10 cm). It was found space correlation between the Productivity of the Soy and the Density of the Soil in the two studied depths and also between the Productivity and the attributes Microporosidade (0 - 10 cm), Macroporosidade (10 - 20 cm) and Total Porosity of the Soil (10 - 20 cm). Therefore, it was considered appropriated the use of geostatistic for this study.